2018
DOI: 10.1007/s10517-018-4070-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidized Dextran on Cytokine Production and Activation of IRF3 Transcription Factor in Macrophages from Mice of Opposite Strains with Different Sensitivity to Tuberculosis Infection

Abstract: We studied differences in the production of pro- and anti-inflammatory cytokines and IRF3 transcription factor by peritoneal macrophages from mice of opposite strains CBA/J and C57Bl/6 and the effect of 60-kDa oxidized dextran on these parameters. Macrophages from C57Bl/6 mice were mainly characterized by the production of proinflammatory cytokines TNFα, IL-12, and MCP-1 (markers of M1 polarization). By contrast, CBA/J mice exhibited a relatively high level of anti-inflammatory cytokine IL-10 and lower express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A number of scholars have previously demonstrated that C57Bl/6 and CBA mice have opposite properties. The differences consisted in varied reactivity of the immune system, the system of mononuclear phagocytes, and their regulation [7]. Furthermore, the responses of the immune and hormonal systems of CBA and C57Bl/6 mice to bacterial and fungal agents, M. tuberculosis [8] and C. albicans [1], were also different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of scholars have previously demonstrated that C57Bl/6 and CBA mice have opposite properties. The differences consisted in varied reactivity of the immune system, the system of mononuclear phagocytes, and their regulation [7]. Furthermore, the responses of the immune and hormonal systems of CBA and C57Bl/6 mice to bacterial and fungal agents, M. tuberculosis [8] and C. albicans [1], were also different.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the responses of the immune and hormonal systems of CBA and C57Bl/6 mice to bacterial and fungal agents, M. tuberculosis [8] and C. albicans [1], were also different. CBA and C57Bl/6 mice are opposite in a number of ways: according to such properties as activity of metabolic processes in the liver [9], sensitivity to infectious agents [10, 11], structural and functional characteristics of the adrenal cortex [9], quantitative representation of cells of the mononuclear phagocyte system in various organs [12], and activation of immune cells [7]. According to the previously described interline differences, it can be assumed that mammals with different genetic programs have different ways of responding to the immune system.…”
Section: Introductionmentioning
confidence: 99%